The Prevalence, Magnitude, and Reversibility of Elevated Liver Enzyme Activities in Hyperthyroid Cats Presenting for Iodine-131 Treatment - Campbell, Joseph; Chapman, Peter; Klag, Alan (Frontiers in Veterinary Science, 2022)
Abstract: Objectives: The primary objective of this study was to report the prevalence and magnitude of elevated liver enzyme activity in feline hyperthyroidism using a large cohort of cats presenting for iodine-131 treatment. The secondary objective was to determine if elevated liver enzyme activity was a reversible process following successful iodine-131 treatment. Methods: Cases that presented for a single iodine-131 treatment were retrospectively reviewed. Short-term and long-term follow up clinicopathologic data was then reviewed for the secondary objective. Results: 217 hyperthyroid cats met the inclusion criteria for the primary objective. 123/217 (56.7%) of the cats had at least one liver enzyme elevation on their chemistry panel, with alanine transaminase activity being the most common. All cats who were successfully treated with iodine-131 had liver enzyme activity within the reference range at short term follow up and long term follow up points. Conclusion and Relevance: Our study demonstrates that elevated liver values are common in cats presenting for iodine-131 treatment. Additionally, our study demonstrates that even when liver values are markedly elevated prior to treatment, the liver enzyme activity will return to normal after successful resolution of hyperthyroidism using iodine-131 treatment. Investigation into hepatobiliary disease and liver function tests for cats with a diagnosis of hyperthyroidism may be unnecessary as the liver values will likely return to normal with successful iodine-131 treatment.